"Influence of flight angle of field synergy elongation element on performance of screw" - HUANG Shi-zheng1, PAN Wei1, ZHU Jia-wei1, YANG Wei-min2, ZENG Xian-kui1, JIAN Ran-ran1,2,3 (Hecheng xiangjiao gongye)
Based on principle of polymer field synergistic plasticization, transportation and mixing, a new structure of field synergy elongation element was designed and developed to enhance mixing and heat transfer. The fluid dynamics simulation software ANSYS Polyflow was used to numerically simulate ordinary threaded screws and field synergy elongation element with different flight angle. The effects of the flight angle on mixing performance, heat transfer performance, and plasticization uniformity of the field synergy elongation element were compared and analyzed. The results showed that the comprehensive performance of the field synergy elongation element was superior to that of the ordinary threaded screw. Among them, the comprehensive performance of the field synergy elongation element was optimal when the flight angle is 45°. The radial convergence channel of the field synergy elongation element changed the direction of the velocity field, causing the velocity vector to generate radial components, promoting the synergistic interaction between the velocity field, temperature gradient field, and velocity gradient field, and strengthening the heat and mass transfer and transportation process. Its unique structure achieved effective mixing of local heat and particles, enhancing the plasticizing effect of mixing and improving the plasticizing quality of the rubber mate-rial.